2017
DOI: 10.1080/0142159x.2017.1372563
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of sequencing virtual patients with lectures in a deductive or inductive learning approach

Abstract: Sequencing VPs in inductive and deductive learning approaches leads to no significant differences on students' performance when full guidance is offered in the inductive approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Huwendiek et al (2013) showed that fifth-year students preferred having a lecture that is followed by VPs, a small group discussion, and then a real patient session. Marei et al (2017) reported no significant difference between sequencing VPs before the lecture (inductive learning approach) or after it (deductive learning approach) on students' performance when direct instruction is offered in the inductive approach to novice learners.…”
Section: Practice Pointsmentioning
confidence: 91%
See 1 more Smart Citation
“…Huwendiek et al (2013) showed that fifth-year students preferred having a lecture that is followed by VPs, a small group discussion, and then a real patient session. Marei et al (2017) reported no significant difference between sequencing VPs before the lecture (inductive learning approach) or after it (deductive learning approach) on students' performance when direct instruction is offered in the inductive approach to novice learners.…”
Section: Practice Pointsmentioning
confidence: 91%
“…The sequence of VPs (learning task) and lecture (supportive information) has been evaluated with respect to students' preference and effectiveness (Huwendiek et al 2013;Marei et al 2017). Huwendiek et al (2013) showed that fifth-year students preferred having a lecture that is followed by VPs, a small group discussion, and then a real patient session.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Most students formulated correct diagnostic hypotheses. They were also satisfied with the methodology because it encouraged inductive learning 4 and achieving metacognition. The students felt that the methodology should be permanently implemented in the course as preparation for in‐person patient care (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…The logs for the male and female students who used the application were examined, and no gender related differences were found, although previous studies in literature have reported contrasting findings in this regard (Marei, Donkers, Al-Eraky, & van Merrienboer, 2017). Furthermore, other studies have reported that the higher the cognitive load of students in these applications, the greater the negative effect on their learning experiences (Choi, Lindquist, & Song, 2014).…”
Section: Discussionmentioning
confidence: 95%